High‐dose vitamin D metabolite delivery inhibits breast cancer metastasis - Jiaye Liu; Junyi Shen; Chunyang Mu; Yang Liu; Dongsheng He; Han Luo; Wenshuang Wu; Xun Zheng; Yi Liu; Sunrui Chen; Qiuwei Pan; Yiguo Hu; et al. (Wiley, 2022)
Abstract Besides its well‐known benefits on human health, calcitriol, the hormonally active form of vitamin D3, has been being evaluated in clinical trials as an anticancer agent. However, currently available results are contradictory and not fundamentally deciphered. To the best of our knowledge, hypercalcemia caused by high‐dose calcitriol administration and its low bioavailability limit its anticancer investigations and translations. Here, we show that the one‐step self‐assembly of calcitriol and amphiphilic cholesterol‐based conjugates leads to the formation of a stable minimalist micellar nanosystem. When administered to mice, this nanosystem demonstrates high calcitriol doses in breast tumor cells, significant tumor growth inhibition and antimetastasis capability, as well as good biocompatibility. We further reveal that the underlying molecular antimetastatic mechanisms involve downregulation of proteins facilitating metastasis and upregulation of paxillin, the key protein of focal adhesion, in primary tumors.